Pendampingan Pemanfaatan Google My Maps untuk Meningkatkan Kompetensi Pembelajaran Spasial Guru Geografi SMA di Kabupaten Pringsewu - Widodo, Sugeng; Istiawati, Novia Fitri; Wijaya, Nyokro Mukti; Septiana, Khoirun Najmi (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to assist high school geography teachers in Pringsewu Regency in utilizing Google My Maps as an interactive spatial learning medium in the classroom. This activity is motivated by the still minimal use of digital mapping technology in classroom learning by geography teachers. The method used is participatory mentoring with a Participatory Action Research (PAR) approach. The subjects of the activity are high school geography teachers, especially those who are members of the MGMP Geography Pringsewu Regency. The activity is carried out through several stages, namely planning, capacity building, implementation of mentoring, and evaluation and reflection. Measurement of the success of the activity is carried out descriptively-qualitatively through observation, discussion, and analysis of digital map products produced by teachers. The results of the activity show an increase in teachers' abilities in designing and using Google My Maps-based digital maps, as well as a growing awareness of the importance of spatial-based learning. Thus, mentoring the use of Google My Maps is effective as a strategy to strengthen the spatial learning competencies of geography teachers.